METHODS AND APPROACHES IN TEACHING ENGLISH FOR MEDICAL STUDENTS AND HEALTHCARE WORKERS (Eureka Journal of Education & Learning Technologies, 2026)
The effectiveness of English language instruction for medical students and healthcare workers depends on the selection of appropriate teaching methods and approaches that address both linguistic and professional needs. This paper explores the main methods and approaches used in teaching English for Medical Purposes (EMP), including communicative language teaching, task-based learning, content-based instruction, problem-based learning, and technology-enhanced learning. Particular attention is given to the development of professional communication skills, medical terminology, and practical language competence required in clinical and academic settings.
Keywords: English for Medical Purposes (EMP), medical English, healthcare workers, medical students, communicative language teaching, task-based learning, content-based instruction, professional communication, medical terminology, language competence, healthcare education, technology-enhanced learning.